Soluble ST2 and renal function in ischemic heart failure with atrial fibrillation - Lashkul, D.; Лашкул, Дмитро Андрійович (My University, 2021)
Soluble ST2 (sST2) is a novel cardiac biomarker whose concentration rises in response to myocardial strain. The aim of this study was to analyse the relationship between soluble ST2 (sST2) level and renal function in heart failure (HF) patients with atrial fibrillation (AF).
Keywords: Type of funding sources: None.; heart failure